THE EFFECT OF PREVENTIVE AND REHABILITATIVE EXERCISES FOR THE ANKLE JOINT ACCORDING TO SOME BIOMOTOR ABILITIES OF YOUNG HANDBALL PLAYER - Dr. Nawfal Dakhil (Galaxy International Interdisciplinary Research Journal, 2024)
Sports training and sports medicine are considered important and specialized basic sciences, in which medical sciences are used and applied from a preventive and rehabilitative perspective, as these sciences have contributed to developing and codifying training loads to be more appropriate to the body’s endurance capacity and to benefit from the positive effects of the body’s functional condition. The importance of the research lies in providing preventive and rehabilitative exercises that contribute to reducing the possibility of players suffering from injuries to the joint itself in advanced age stages, through their impact on some of the abilities of the ankle joint by strengthening the muscles working on it. The problem of the research was the following questions: What is the reality of the biomotor capabilities of young handball players and how to avoid joint sprain injuries and weakness of the working muscles and ligaments on the joint (muscle imbalance). The objectives of the research were: preparing preventive exercises for the ankle joint according to the biomotor capabilities of young handball players and identifying... The effect of preventive exercises on the ankle joint. The researcher assumed that there were statistically significant differences between the results of the pre- and post-tests for the ankle joint according to bio-motor abilities. The researcher used the experimental approach by designing the two equal groups, the control and the experimental, to suit the nature and problem of the research. The research sample was made up of young players belonging to the Samawa Sports Club, numbering 16 players, and they were divided. It was divided into two experimental and control groups, where the number of each group was 8 players. The researcher concluded that preventive exercises have a positive effect on reducing the incidence of injuries to the ankle joint (sprain, minor tear, and muscle weakness). There is a positive effect of preventive exercises on the biokinetic capabilities of the muscle group working on the ankle joint. The researcher recommended using special preventive exercises for the lateral ligaments of the knee joint to prevent injuries (sprains, minor tears, and muscle weakness), preparing special preventive exercises and the necessity of the trainer and physical therapist participating due to the importance of determining the type of muscle weakness that needs to be strengthened or the type of exercises required, their intensity, repetitions, and duration of rest.